(a/(b+2c+3d))+(b/(c+2d+3a))+(c/d+2a+3b))+(d/(a+2b+3c))>=2/3 不等式证明
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 00:54:25
(a/(b+2c+3d))+(b/(c+2d+3a))+(c/d+2a+3b))+(d/(a+2b+3c))>=2/3不等式证明(a/(b+2c+3d))+(b/(c+2d+3a))+(c/d+2a+
(a/(b+2c+3d))+(b/(c+2d+3a))+(c/d+2a+3b))+(d/(a+2b+3c))>=2/3 不等式证明
(a/(b+2c+3d))+(b/(c+2d+3a))+(c/d+2a+3b))+(d/(a+2b+3c))>=2/3 不等式证明
(a/(b+2c+3d))+(b/(c+2d+3a))+(c/d+2a+3b))+(d/(a+2b+3c))>=2/3 不等式证明
b+2c+3d=t-----b=t-2c-3d
c+2d+3a=z -----c=z-2d-3a
d+2a+3b=m ------d=m-2a-3b
a+2b+3c=n
d+2a+3b=d+2a+3t-6c-9d=2a+3t-6c-8d=m
c+2d+3a=a+2t-4c-3d+3c=a+2t-c-3d=a+2t-z+2d+3a-3d=4a+2t-z-d=6a+2t-z-m+3b=n
6a+3b=z+m+n-2t=c+2d+3a+d+2a+3b+a+2b+3c-2b-4c-6d=6a-3d+3b -----d=0
将d=0代入原式,得
a/(b+2c)+b/(c+3a)+c/(2a+3b)
接下来用不等式公式
柯西不等式
计算:a^3(b+c-d)+a^2b(c+d-a)-a^2c(d+a+b)
(a-2b+3c/a+b-c)-(a-b+c/a-c+b)+(2c-d/c-a-b)化简结果
A:B=C:D 求 2A-B/3B+A 和 C+3B/D-C
若a/b=b/c=c/d,且a-b+c-d=0,则3a+2b+c/a-2b-3c=
计算:(a+b-c)^2 计算:(a+b-c)^2 和(a-b+c)(a-b-c)和(a-b-c)(a+b+c) 和 (a+b-c)(a-b+c) 和 (a-b+c-d)(a-b-c+d)
已知:a/b=c/d,求证:(2a+3b)/(a+b)=(2c+3d)/(c+d)
a-b=2,b-c=-3,c-d=5,求(a-c)*(b-d)除以(a-d)
A B C D
A B C D
(a+b)(c+d).
[a,b)×[c,d
a,b ,c ,d
a b c d
(a) (b) (c) (d)
A,B,C,D
A B C D
(a+b)^2-c^2 分解结果为:(请写下过程)A.(a+b-c)(a-b+c)B.(a+b+c)(a+b-c)C.(a+b+c)(a-b-c)D.(a-b+c)(a-b-c)
观察:a+(2b-3c)=a+2b-3ca-(2b-3c)=a-2b+3c求a-b+c=a-( ) (a-b+c-d)(a+b-c+d)=[a-( )][a+( )]